Continuous for Live Load Steel Girder Construction in the Northern Panhandle of West Virginia - Ream, Anthony; Beining, William (Engineering Journal, 2014)
This paper presents two recently constructed steel girder bridges in the northern panhandle of West Virginia featuring simple for dead load—continuous for live load (SDCL) construction. The design, fabrication, construction and maintenance of this structure type are explored in addition to positive impacts on traffic control.